6 Degree-of-Freedom Force-Torque Sensor based on Electromagnetic Force Compensation - Bae, Yeeun; Yoon, Kyung Taek; Lim, Hyunho; Choi, Young Man (Proceedings - ASPE 2023 Annual Meeting, 2023)
Multi-degree-of-freedom ultra-precision force sensors are widely used in industrial applications such as biomedicine, precision chemistry, semiconductor manufacturing and so forth [1]. Among force measurement methods, the electromagnetic force compensation principle is the state-of-art, which has high resolution and good repeatability down to μN. This paper proposes a novel six degrees-of-freedom electromagnetic force compensation force-torque sensor based on crab-leg compliant mechanism and voice coil motors.
Keywords: 6 degree of freedom; Electromagnetic force compensations; Force-measurement method; Force/torque sensor; High resolution; Multi degree-of-freedom; Semiconductor manufacturing; Six degrees of freedom; Ultra precision; Voice coil motors